Comparison of Colonic J-pouch and Straight Coloanal anastomosis after Low Anterior Resection - Mehrvarz, Shaban (Kowsar, 2013)
BACKGROUND: The tendency towards sphincter preserving for low rectal cancers with low anterior resection, has led to the technique of straight coloanal anastomosis (SCAA) or colonic J-pouch anal anastomosis (CPAA). OBJECTIVES: The aim of our study was to compare functional outcomes, complication rates and quality of life (QoL) after LAR with either a straight or colonic J pouch anastomosis. PATIENTS AND METHODS: In 88 patients with rectal tumors located in lower third, who were candidate for LAR with coloanal anastomosis. They were divided for reconstruction using either SCAA (n= 47) or CPAA (n= 41) from January 2007 to May 2009. Functional results were assessed after closure of temporary loop ileostomy, 6 months postoperatively. Quality of life (QoL) was measured using European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30. RESULTS: The two groups were matched for gender, age, and preoperative chemotherapy and radiotherapy. There were no significant differences between the SCAA and CPAA groups relative to anastomotic leakage. Among patients with CPAA, the mean of 24 hours bowel movements, daytime bowel movements, incontinence scores, and incidence of urgency were significantly lower than those in the SCAA group. Also, patients with a CPAA had a significantly better quality of life. CONCLUSIONS: CPAA provided not only better functional results than SCAA, but also improved quality of life, thus may be the better choice.